Efektivitas Media Aplikasi Ruangguru terhadap Hasil Belajar Matematika Siswa Kelas V SDN 146 Bengo Kecamatan Bengo Kabupaten Bone - Awaluddin Muin; Firdaus Firdaus; asmira mira shari (Universtas Negeri Makassar, 2023)
This research is a type of quantitative research with a pre-experimental research design. The purpose of this study was to determine students' mathematics learning outcomes and to find out the significant differences before and after using the Ruangguru application media. The research design used was One-Group Pretest-Posttest Design.. Data collection techniques are learning outcomes tests to measure student learning outcomes before and after using the Ruangguru application media. The data analysis used is descriptive statistical analysis which obtains an average pretest of 30.33 which shows student learning outcomes before learning using the Ruangguru application media are in the less category and the posttest average is 80.83 which indicates that student learning outcomes after learning using the Ruangguru application media was in the good category, and inferential statistical analysis obtained N-Gain data, namely 0.7301 which was included in the high category. The results of the study showed that there were significant differences before and after learning using the Ruangguru application media on the mathematics learning outcomes of fifth grade students at SDN 146 Bengo, Bone Regency.